Semiconductor Based on Oil Palm Empty Fruit Bunch Alkali Cellulose - Adiati, Rima Fitria; Nikmatin, Siti; Irmansyah, - (Universitas Muhammadiyah Yogyakarta, 2024)
Oil palm empty fruit bunch (OPEFB) is a readily available biomass resource in Indonesia. Its processing into alpha-cellulose and alkaline cellulose offers promising economic opportunities and sustainable sensor development. This study focuses on extracting alpha-cellulose from OPEFB using kraft hydrolysis method and converting it into alkaline cellulose using NaOH solution. The 15, 20, and 25% variation of NaOH percentage during pulping resulting in different pulp quality indicated by alpha-cellulose content. The resulting alkali cellulose exhibits semiconductor properties with an energy gap of 3.6 eV, demonstrating its potential for light sensor or photodiode applications. Additionally, the optical energy gap of alkali cellulose-polyvinyl alcohol composites is investigated.